Study and Evaluation of Loss Circulation Mitigation When Drilling Unconsolidated Formation, Batang Field - Wewen Afterian; KRT Nur Suhascaryo; Suranto Suranto (Journal of Petroleum and Geothermal Technology, 2022)
Field development of Batang Field through infill drilling was an effort by PHE Siak to contribute to national oil production. Target formation of the drilling campaign was Bekasap Formation which is part of central Sumatera basin. During the drilling execution of these infill wells, loss circulation occurred on some of the wells especially when the drilling reaches 8.5 in hole section. The severity of loss circulation ranging from small partial loss to total loss. To optimize future drilling operation in Batang, analysis will be conducted to determine the cause, prevention, and mitigation of loss circulation event based on drilling history.Method used in this research begins with analysing the cause of loss circulation on 8.5 in hole section that commonly occurs. Analysis then proceeded to analyse historical drilling parameter, such as: pump (MW, ECD, Pump Rate, Yp, RPM, SPM, dan ROP) recorded when loss circulation events occurred. Finally, the effectiveness of current method to mitigate loss circulation will also studied.Based on the analysis, it is known that the possible cause of loss circulation on infill well drilling in Batang is the reservoir properties and condition which having depleted or sub-normal average reservoir pressure and the property of the rock itself which is unconsolidated. Based on the study on drilling parameter history, the severity of loss circulation might be minimized by keeping pump flow rate to under 190 gpm, RPM under 48 rpm, WOB under 2 klbs, and ROP under 135 ft/hr when drilling progresses to 8.5 in hole section. Meanwhile, other parameters have not shown any relation to severity of loss circulation.